The changing context of walking behavior: coping with the COVID- 19 Pandemic in urban neighborhoods - Lotfata, Aynaz; Gemci, Ayse Gul; Ferah, Bahar (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose - It is observed that the COVID-19 Pandemic mostly restricts people's movement and walking habits. In this direction, this study aims to highlight how the walking behaviors of individuals affected in different geographies' neighborhoods before and during the Pandemic. Design/methodology/approach - This paper focuses on the relationship between neighborhood characteristics and the changing walking behavior of 24 sample regions (514 participants) with the highest incidents of COVID-19 infection from American, European, Asian, Western Pacific, African and Middle Eastern cities. The paper's methodology is supported by an /online questionnaire survey conducted in these 24 disparate neighborhoods in December 2020. Findings - Findings show that walkable access varies over geographies during the Pandemic. Urban amenities within 15-20 min of access become more important than ever. The results unravel that either walkable or non-walkable neighborhoods showcased similarities despite that urban amenities were not within 15-20 min of access. Three prominent aspects should be emphasized to plan walkable neighborhoods: providing walkable access, forming spatial proximity and sustaining social cohesion. Social implications - The availability of daily amenities, such as shopping stores, health care, education services and pharmacies within a 15-20-min walking distance maintain everyday life and increase social interactions. In addition, places with walkable access encourage an active lifestyle and contribute the public health. The impact of the COVID-19 Pandemic movement restrictions on the walking behavior of individuals highlights how the qualities of distance-based urban planning need to be supported with time-based practical attributes that can shape neighborhood planning frameworks. Originality/value - This paper highlights the coexistence of walkability and accessibility measures in urban practice and research to create resilient and sustainable neighborhoods. The walkable access term used in the paper addresses joint measures of walkability and accessibility.
Keywords: Walkability; Walkable access; 15-20-minutes neighbourhoods; The COVID-19 Pandemic; MOBILITY; TRAVEL; Architecture